New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China - Xing, Changyue; Shih, Chungkun; Zhao, Yunyun; Ren, Dong (Zootaxa, 2016)
Two new genera, each with a new species, Perissoderma triangulum gen. et sp. nov. and Abrderma gracilentum gen. et sp. nov., of the family Protodiplatyidae are described from the latest Middle Jurassic Jiulongshan Formation of Daohugou, Inner Mongolia, China. They are the first records of Protodiplatyidae from the latest Middle Jurassic Daohugou locality. Both new genera are assigned to Protodiplatyidae based mainly on diagnostic characters of antennae, pronotum, tegmina, tarsi and the distinct long, slender, multi-segmented cerci. We summarize the distributions and ages of all described fossil Archidermaptera and infer that the Dermaptera might have originated in Eurasia and started their diversification and migration to a worldwide distribution. The new taxon of Abrderma gracilentum gen. et sp. nov. provides one more example of an early earwig with well-preserved pentamerous tarsi on the hind leg.